Pemberdayaan Siswa Melalui Pelatihan Tentang Asma Brochial Meminimalkan Kejadian Covid-19 di MAN 1 Muara Bungo - Hani Ruh Dwi (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2021)
Background: Empowerment is providing resources, opportunities, knowledge, and skills to citizens to increase their ability to determine their own future and participate in efforts to influence the lives of their groups, by applying the knowledge correctly they already have. Students are considered the most appropriate people to impart the knowledge they have acquired, both to the family and the wider environment. Asthma does not make a person more susceptible to contracting the corona virus, but unfortunately if people with lung conditions such as asthma get the corona virus, their condition can be more severe. Purpose;The goals achieved in this health education activity   are: the community understands about empowerment, the community understands about bronchial asthma, the community understands about covid-19. Method; The method is given by means of lectures, question and answer and discussion (CTD) to students about student empowerment through training on brochial asthma to minimize the incidence of covid-19 by using power points and leaflets. Results; The results of the activity were 80%, there was an increase in students' knowledge before and after being given health education, the average increase in knowledge reached an increase of 50%. Conclusion: the students understand the concept of empowerment, students understand the concept of bronchial asthma, students understand about minimizing the incidence of covid-19 :